FAKTOR-FAKTOR YANG MEMPENGARUHI VALUE OF THE FIRM PADA PERUSAHAAN PROPERTI PERIODE 2018-2021 - Tjugito, Shinta; Jonnardi, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
In this research, the aim is to find out and collect the results of data processing regarding the effect of profitability, liquidity, and leverage on the value of the firm with inflation as a moderating variable for property companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. In this study also used secondary data. The sampling technique in this study was using simple random sampling. Meanwhile, the data processing in this study uses the E-Views 12 program. The results obtained from the program explain how the profitability variable has a positive effect on the value of the firm and how the liquidity and leverage variables have a negative effect on the value of the firm. The results of this study also explain how inflation weakens the profitability and leverage variables on the value of the firm and shows how inflation strengthens the liquidity variable on the value of the firm.